Norwegian student teachers’ perspectives on linear equations - Larson, Niclas (NOMAD Nordic Studies in Mathematics Education, 2024)
The topic of linear equations is part of school mathematics all over the world. Hence, it is important that teachers are proficient in teaching equations, explaining not only the arithmetic operations in the solving process, but also the objectives of the solution, the nature of an unknown and the balance property of an equation. This study employs a set of 16 low-inference codes to analyse 146 Norwegian student teachers’ explanations of the solution of a linear equation. One important result is that a majority of the students explained additive operations rather by ”swap sides swap signs” than by ”do the same to both sides”.